Pendekatan Estimasi Kebutuhan Rumah bagi Masyarakat Indonesia melalui Penerapan Matriks Siklus Hidup - Adhar, Khairunnisa; Widyantoro, Bimo Aji (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
This study aims to estimate the gap between the number of available houses and the number needed by the community, often measured through the housing backlog. The housing backlog includes ownership backlog, which is the percentage of households that own their own homes; and occupancy backlog, which is the ideal condition where one house is occupied by one family. With the rapid population growth and urbanization in Indonesia, estimating housing needs becomes crucial to ensure the availability of adequate and decent housing for all segments of society. This research examines approaches that can be used to apply the Life Cycle Matrix (LCM), first introduced in Japan in the 1980s, to estimate housing needs based on changes in household life cycles, such as changes in household size and the age of the household head. The research method used is a quantitative approach with descriptive and analytical methods. The data used are secondary data, namely the Population Census Results from the Central Bureau of Statistics (BPS, formerly known as the Central Bureau of Statistics). The analysis stages include data availability verification and data cleaning. Then, housing backlog calculations are carried out, as well as the development of approaches that can be developed for Estimating Housing Needs for the Indonesian Community through the application of the Life Cycle Matrix.